The value of three-dimensional echocardiography in the diagnosis and management of ruptured sinus of Valsalva aneurysm: a case report. Issue 3 (13th July 2019) - Daud, Elias; Or, Tsafrir; Adler, Zvi; Shturman, Alexander
Abstract: Background : A sinus of Valsalva aneurysm (SVA) is a rare cardiac anomaly. Most SVA's rupture into right heart chambers and can be classified using the modified Sakakibara classification according to the site of rupture. Transoesophageal echocardiography (TOE) is a useful diagnostic tool and aides in treatment planning in patients with congenital anomalies in emergency situations. Three-dimensional TOE (3D-TOE) provides additional value over standard TOE. Case summary: A 38-year-old man with a reported history of ventricular septal defect (VSD) presented to the emergency department complaining of chest pain and epigastric pain lasting several days. Physical examination revealed a continuous heart murmur and signs of acute heart failure. A 3D-TOE revealed an SVA rupture into the right ventricle (Type IIIv) but no evidence of a VSD. Urgent aortic valve replacement with correction of the ruptured SVA was performed. Neither a VSD nor signs of endocarditis were found during surgical exploration. The patient was discharged on post-operative Day 5 in good condition. Discussion: A sinus of Valsalva aneurysm is a rare cardiac condition. Ventricular septal defect, bicuspid aortic valve, or aortic valve regurgitation may coexist with SVA. Xin-Jin et al . classified a ruptured SVA into five types according to the site of rupture. Transoesophageal echocardiography is an important tool for diagnosis, anatomical description, and typing of the ruptured SVA. Sinus of Valsalva aneurysm may be misdiagnosed as a VSD, as was the case in our patient, and 3D-TOE can be instrumental for providing both correct diagnosis and critical surgical planning.